Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/1751-2980.12463
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐1254 inhibits the migration of colon adenocarcinoma cells by targeting PSMD10

Abstract: MiR-1254 may act as a tumor suppressor in CRC and may inhibit CRC migration by directly targeting PSMD10 to suppress the EMT process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Enforced expression of miR-1254 suppressed the migration capacity of colorectal cancan cells by targeting PSMD10, which was an important regulator for epithelial–mesenchymal transition. 17 Similarly, miR-1254 expression was lower in cervical cancer tissues than in adjacent normal tissues. Reduced miR-1254 was positively associated with positive lymphatic invasion, distant metastasis, and advanced International Federation of Gynecology and Obstetrics stage.…”
Section: Discussionmentioning
confidence: 98%
“…Enforced expression of miR-1254 suppressed the migration capacity of colorectal cancan cells by targeting PSMD10, which was an important regulator for epithelial–mesenchymal transition. 17 Similarly, miR-1254 expression was lower in cervical cancer tissues than in adjacent normal tissues. Reduced miR-1254 was positively associated with positive lymphatic invasion, distant metastasis, and advanced International Federation of Gynecology and Obstetrics stage.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that miRNAs act as carcinogenic factors or tumor suppressor factors according to the specific function of targeting mRNA 22,23 . Only a few studies have reported miR-1254 is aberrantly expressed and plays special roles in different malignancies like lung cancer, thyroid cancer, and colorectal cancer 1113 . However, the function of miR-1254 in GC and the potential molecular mechanism remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miRNAs expression promotes the development of cancer due to the activation of oncogenes and silence of tumor-suppressor genes 9,10 . Accumulating evidence has revealed that miR-1254 might strongly correlate to human cancer, such as non-small-cell lung carcinoma, thyroid cancer, and colorectal cancer 1113 . However, the biological functions and molecular mechanisms of miR-1254 in GC have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier investigations carried out on miR-1254 have revealed that it inhibited cell migration and invasion of cancer cells [14]. For instance, miR-1254 has been reported to inhibit the migration and invasion of colorectal cancer by inhibiting PSMD10 [15]. Therefore, the effect of miR-1254 on the migration and invasion of SW 1008 astrocytoma cells was also investigated in the current study.…”
Section: Discussionmentioning
confidence: 86%